A new era of flood control strategies from the perspective of managing the 2020 Yangtze River flood - Xia, Jun; Chen, Jin (Science China. Earth sciences, 2021)
Flood control of the Yangtze River is an important part of China’s national water security. In July 2020, due to continuous heavy rainfall, the water levels along the middle-lower reaches of the Yangtze River and major lakes constantly exceeded the warning levels, in which Taihu Lake exceeded its highest safety water level and some stations of Poyang Lake reached their highest water levels in its history. In August 2020, another huge flood occurred in the Minjiang River and the Jialing River in the upper Yangtze River, and some areas of Chongqing Municipality and other cities along the rivers were inundated, resulting in great pressure on flood control and high disaster losses. The 2020 Yangtze River flood has received extensive media coverage and raised concerns on the roles of the Three Gorges Dam and other large reservoirs in flood control. Here we analyze the changes in the pattern of the Yangtze River flood control by comparing the strategies to tackle the three heavy floods occurring in 1954, 1998, and 2020. We propose that the overall strategy of the Yangtze River flood control in the new era should adhere to the principle of “Integration of storage and drainage over the entire Yangtze River Basin, with draining floods downstream as the first priority” by using both engineering and non-engineering measures. On the basis of embankments, the engineering measures should use the Three Gorges Dam and other large reservoirs as the major regulatory means, promote the construction of key flood detention areas, keep the floodways clear, and maintain the ecosystem services of wetlands and shoals. In terms of non-engineering measures, we should strengthen adaptive flood risk management under climate change, standardize the use of lands in flood detention areas, give space to floods, and promote the implementation of flood risk maps and flood insurance policies. The ultimate goal of this new flood control system is to enhance the adaptability to frequent floods and increase the resilience to extreme flood disasters.